Prevalence of hepatitis B virus infection among persons with hepatitis D virus and diabetes mellitus in Pakistan, 2019-2021 - Ahmad Raza; Muhammad Waqar Mazhar; Saira Saif; Mudasara Sikandar; Iram Shahzadi; Javaria Mehmood; Wajeeha Iram; Hira Tahir; Shanzab Noor; Fatima Mazhar (Archives of Hepatitis Research - Peertechz Publications, 2022)
Introduction: The HBV virus has its enveloped protein that surrounds nucleic acid for its protection. Hepatitis B DNA virus belongs to the Hepadnoviridae family and is similar to retroviruses. Globally, HBV infected people approximately 2 billion in the world, about 350 million people were chronic carriers. One million deaths are caused by the HBV virus every year. Each year, 400,000 new cases were reported in Latin America. Among all over the World, Pakistan was considered as one of the largest chronic viral hepatitis infection countries. Methodology: 975 samples were recoded from different districts of south Punjab. The sera of the patient's sample were examined to analyze the LFTs, HBS serology, HBS ELIZA, anti-HBeAg, AFP, anti- HDV, HBC IgM, and HBV DNA EAL TIME PCR. An anticoagulant sample was used to analyze their prothrombin time, HB level, WBC count, PLT counts, and HBA1C. Data were analyzed by using Microsoft Excel 2019 and SPSS version 14.0.  Results: 975 samples were collected from the Multan district of Punjab. Out of which 638(65.43%) patients were detected positive for HBsAg serology, 312(32.84%) were not detected. The HBA1C test values are higher in HBV patients and its normal value is below 6.4%. In 1st group 258 patients out of 638 are HBV PCR DETECTED, bilirubin 2.1+-5.7, ALP 425.1±575.1, AST 119.6±102.6, ALT 62.0±41.6, and albumin 3.5±0.9. in the 2nd group, 149 patients out of 638 are HBV PCR detected, bilirubin 1.4±1.9, ALP 488.1±339.2, AST 143.0±117.4, ALT 78.1±53.4, and albumin 4.4±0.6. Conclusion: The prevalence of HBV in diabetic patients is higher as compared to control diabetic patients. the patients with high serum AFP levels tend to be HBs-Ag-positive, and those who have low AFP levels are associated with cryptogenic cirrhosis. The positive HBc IgM is higher in anti-HDV-negative cases as compared to HDV-positive cases. The value of HBV DNA was higher in anti-HDV-negative cases. The HBsAg correlates with HBV DNA level and it's a level higher in the IT phase and lowers in the IC phase.